The role of family in the formation of learning motivation for adolescents - Sharafitdinov Abdulla XXX; Qarshiboyev Sardor Alisher ugli (Zien Journals, 2022)
This article focuses on the role of family in the formation of learning motivation for adolescents and its family-related aspects. Attempts have been made to reveal specific social and psychological reasons that need to be taken into account in the process of shaping learning motivation in the parent-child relationship.
Keywords: Adolescence; motivation; learning activities; understanding of motives